Evaluación de las prácticas verdes y su influencia en el desempeño operacional de los restaurantes de la ciudad de Manta - Barre Zavala, María José (2019)
The subject of study the evaluation of green practices and their influence on the operational performance in the restaurants of the city of Manta, the titling work allowed to generate knowledge in the authors, their problem was that the restoration sector uses energy with greater intensity, using three times more energy per square foot than most other sectors, which is why restaurants should carry out activities that reduce the negative environmental impact; The methodology that was used to develop the proposed evaluation was through the different methods used such as the analytical, descriptive, statistical and correlation methods, types of research were used such as: bibliographic, field, descriptive, exploratory research and techniques such as observation, survey which was applied to the different managers of the restaurants of the city of Manta that was measured through the Likert scale, then we proceeded to enter the data of the tabulated surveys to the SPSS Software this favored efficiently in the analysis of the data collected, responding to the research unknown; In addition, the reliability of Cronbrach's Alpha was known which allowed validating the degree to which the instruments have measured the information according to the Likert scale, it is important to mention that Pearson's test was used in the investigation, it helped to make a comparison between the variables identified allowing to know the degree of influence that these have within the object of study.